Dysbiosis of upper respiratory tract microbiota in elderly pneumonia patients - de Steenhuijsen Piters, Wouter A. A.; Huijskens, Elisabeth G. W.; Wyllie, Anne L.; Biesbroek, Giske; van den Bergh, Menno R.; Veenhoven, Reinier H.; Wang, Xinhui; Trzcinski, Krzysztof; Bonten, Marc J.; Rossen, John W. A.; Sanders, Elisabeth A. M.; Bogaert, Debby (Oxford University Press, 2016)
Bacterial pneumonia is a major cause of morbidity and mortality in elderly. We hypothesize that dysbiosis between regular residents of the upper respiratory tract (URT) microbiome, that is balance between commensals and potential pathogens, is involved in pathogen overgrowth and consequently disease. We compared oropharyngeal microbiota of elderly pneumonia patients (n=100) with healthy elderly (n=91) by 16S-rRNA-based sequencing and verified our findings in young adult pneumonia patients (n=27) and young healthy adults (n=187). Microbiota profiles differed significantly between elderly pneumonia patients and healthy elderly (PERMANOVA, P<0.0005). Highly similar differences were observed between microbiota profiles of young adult pneumonia patients and their healthy controls. Clustering resulted in 11 (sub)clusters including 95% (386/405) of samples. We observed three microbiota profiles strongly associated with pneumonia (P<0.05) and either dominated by lactobacilli (n=11), Rothia (n=51) or Streptococcus (pseudo)pneumoniae (n=42). In contrast, three other microbiota clusters (in total n=183) were correlated with health (P<0.05) and were all characterized by more diverse profiles containing higher abundances of especially Prevotella melaninogenica, Veillonella and Leptotrichia. For the remaining clusters (n=99), the association with health or disease was less clear. A decision tree model based on the relative abundance of five bacterial community members in URT microbiota showed high specificity of 95% and sensitivity of 84% (89% and 73%, respectively, after cross-validation) for differentiating pneumonia patients from healthy individuals. These results suggest that pneumonia in elderly and young adults is associated with dysbiosis of the URT microbiome with bacterial overgrowth of single species and absence of distinct anaerobic bacteria. Whether the observed microbiome changes are a cause or a consequence of the development of pneumonia or merely coincide with disease status remains a question for future research.
Keywords: Taverne; Journal Article; Research Support, Non-U.S. Gov't